Sexual care for patients receiving dialysis: A cross‐sectional study identifying the role of nurses working in the dialysis department. (8th August 2017) - van Ek, Gaby F.; Gawi, Adina; Nicolai, Melianthe P. J.; Krouwel, Esmée M.; Den Oudsten, Brenda L.; Den Ouden, Marjolein E. M.; Schaapherder, Alexander F.; Putter, Hein; Pelger, Rob C. M.; Elzevier, Henk W.
Abstract: Aims: To explore the role of nurses in the dialysis department in providing sexual care to patients receiving dialysis. Background: Sexual health is not self‐evident for patients undergoing dialysis; 70% experience sexual dysfunction. Nevertheless, sexual care is often not provided. Design: A national cross‐sectional survey. Methods: Questionnaires ( n  = 1211) were sent to employees of 34 dialysis centres from January–May 2016. Descriptive statistics and statistical tests were used to describe and interpret data. Results: The response rate was 45.6%. Three‐quarter of nurses discussed sexual dysfunction with less than half of their patients. Main barriers for discussing were based on language and ethnicity (57.3%), culture and religion (54.1%) and the older age of the patient (49.7%). Eighteen per cent of nurses had sufficient knowledge on sexual dysfunction, competence was present in 51.2% of nurses and 68.3% indicated a need for training. Forty‐three per cent knew about guidelines on sexual care by renal care providers. Nurses who rated their knowledge or competence higher or who were aware of guidelines discussed sexuality more often. The accountability for discussing sexuality was appointed to nephrologists (82.8%) and their own group of professionals (66.3%). Nurses referred 1.16% of their patients to sexual care providers. Conclusion: Dialysis nurses do not consistently address patients' sexuality, although they feel accountable to do so. This seems due to self‐imposed insufficient knowledge, cultural barriers and organizational problems. Study findings imply that current situation could benefit from guidelines, additional training, a private moment to discuss sexual dysfunction and adequate referral systems to specialized care providers.